Knowledge, attitude and practice regarding family planning among the reproductive age women of Khopasi, Kavrepalanchowk - Manandhar, Naresh; Amatya, Isha; Gautam, Arundhati; Kumar, Gaurav; Ahlawat, Himanshu; Adhikari, Nitesh; Mahaseth, Pawan Kumar (Journal of Chitwan Medical College, 2020)
Background: Uncontrolled population growth has been a problematic issue all over the world. Knowing the women’s and their husband’s knowledge and attitude towards family planning may help to intervene so that the practice can be increased. This might ensure the right of women to have child as they wish and later reduce unwanted pregnancies and abortions. Hence the present study is concerned with knowledge and attitude of women towards family planning. Methods: A cross-sectional study was conducted during 10th-15thNovember 2019 among women of reproductive age of Khopasi, Kavrepalanchowk. Structured questionnaire consisting of knowledge, attitude and practice regarding family planning was administered to reproductive women age. Results: All respondents heard about the family planning methods. More than 90% of respondents knew about Norplant, Pills, Depo-Provera and condoms.60.8% respondents were currently using family planning methods. It has been observed that the respondents had positive attitude towards family planning. Conclusions: Knowledge about family planning methods was good among the reproductive age women whereas the practice and attitude seemed satisfactory. The knowledge about emergency contraceptive and abortion were poor among the reproductive age women. One of the promising findings of the study was, the majority of respondents showed a positive attitude towards contraceptive use. There is need to target these population for health education interventions in order to achieve the desirable practices.